An event-related potential study of the relationship between N170 lateralization and phonological awareness in developing readers. (October 2016) - Sacchi, Elizabeth; Laszlo, Sarah
Abstract: As reading development progresses, the visual processing of word forms becomes increasingly left-lateralized. This is visible, among other ways, as increased left-lateralization of the N170 ERP component. A primary explanation of this effect, the phonological mapping hypothesis, proposes that the left-lateralization of visual word form processing that accompanies reading development is the result of calling upon left hemisphere auditory language regions to perform the linking of orthography with phonology (phonological mapping). A key, but untested, prediction of the phonological mapping hypothesis is thus that individuals with greater phonological awareness should exhibit more left lateralized visual processing of word forms than individuals with poorer phonological awareness. We set out to test this hypothesis here. We accomplished this by collecting ERPs while children grades 5–6 viewed words, objects, and word/object ambiguous items (e.g., "SMILE" shaped like a smile - hereafter referred to as wobjects ). Results revealed that, consistent with the phonological mapping hypothesis, individual phonological awareness (but not other measures of reading development) predicted left-lateralization of the N170 component elicited in response to words (but not item types that were not word-like). Highlights: Phonological awareness (PA) predicts left-lateralization of orthographic decoding. Left-lateralization of early wordform processing is specifically linked to PA. Low-ability readers display weak cortical specialization for visual word forms.